New analysis of variability of rower`s technique - Kleshnev, V. (BioRow, 2024)
Our previous analysis of the variability in rowers' motions (RBN 2024/06) was based on variations between stroke cycles at each data point for each biomechanical variable. While that method provided valuable insights, it did not allow for the analysis of between-channel variation. This limitation made it impossible to assess the variation of derived indicators (such as Catch and Rowing Style Factors) and the synchronization of rowers within a crew (e.g., how consistently rowers match the timing of direction changes at the catch).